SÍFILIS: UMA REVISÃO DA LITERATURA - De Oliveira, Marlene De Fátima Daronco; De Araujo, Franciele; Scherer, Karen; Frizzo, Matias (Salão do Conhecimento, 2019)
Trabalho apresentado na disciplina de Biotecnologia